THE APPROACH TO THE CONCEPT OF REPENTANCE OF IMAM GHAZALI IN İHYA-U ULÛMÎ’D-DİN - İbrahim ÇELİK (Fırat University, 2019)
As a Word, return path used in the sense of the Word repent is giving up the sins penitentially. In this way, through the use of Quran Tevbe-i Nasuh means that people of the sins he has committed in the past with sincere regret by a volunteer, intending not to commit this sin again in the future. In the Quran, after he makes the first mistake, with God’s error, and also it is described that he is donated. With this verse and smiliar verses, Allah has encouraged people to repent and to seek ways by giving up their sins for people to get rid of perdition. The Prophet Mohammad also has pointed to his ummah the repentance as a way of salvation. In this way, his precious companions have guided to the Muslims provided that they are applied to repentance. In the field of Islamic sciences, the concept of repentance has been dealt with different aspects of and also evaluations are made on. Scholarly commentary reviews the use of repentance in the Quran and İslamic scholars have examined the the repentance in the place of the words, acts and representation of the Prophet Mohammad. On the other hand kalam scholars have interpreted the theological aspects of the human condition repents. Sufis also interms of their methodology have reviewed the meaning of the term pledge, what the cases requiring repentance are, the time to repent, the conditions and degress of repents by taking different approaches. As the general, Imam Ghazali in which some of the Sufishave handled the pledge as the regrets from the sins of the people and also evbe is the term that guardians regrets from their mistakes as their location and also inabe is used for the repentance of the prophets. Imam Ghazali indicates that every man should repent with fulfilling the conditions and also should not delay it and deposited delaying repentance of sins cause that people sentence to perdition. Imam Ghazali who discusses whether to accept the repentance of has adjudged that fulfilling the conditions of repentance will be accepted by God. Imam Ghazali evaluates repents depending on whether to proceed to repentance and gradates them as follows: 1. Those who are constantly in repentance 2. Those who restart to commit sins again after repentance continued resolutely 3. Disturbers of repentance that repent immediately after.